Pengaruh Video Konten Tutorial Kecantikan Di Tiktok Terhadap Minat Rias Followers @Focallure.Live - Santoso, Shannon; Nurhajati, Lestari (Jurnal Pustaka Komunikasi, 2024)
Visual communication through social media has become an integral part of today's digital culture, with beauty tutorial content on platforms like TikTok gaining significant popularity. However, few studies have paid attention to the impact of beauty tutorial content on TikTok on the makeup interest of followers on the @focallure.live account. The purpose of this study is to find out the influence of beauty tutorial content videos on TikTok on the interest of @focallure.live followers in makeup. A quantitative approach was used in this study, with data collected through questionnaire filling. Data analysis includes testing of instruments, validity, reliability, normality, coefficient of determination, simple linear regression analysis, and testing of partial hypotheses. The results of the study show that the content of beauty tutorials significantly affects the makeup interest of followers of the @focallure.live account. It was found that the variables Providing Information and Explaining the Process in the tutorial video had the greatest influence on makeup interest. The study concluded that beauty tutorial content on TikTok plays an important role in shaping the makeup interest of @focallure.live account followers. These findings provide deeper insights into the impact of social media on consumer behavior in the beauty industry.